LAPORAN KEUANGAN PEMERINTAH - Agung Darono (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2011)
Berger and Luckman (1990) defined contruction of reality as an angoing dynamic process that is (and must be) reproduced by people acting on their interpretations and their knowledge of it. In this view, the term of"goverment financial statement" and various other terms assosiated with it, is a social contruction. This paper, by using discourse analysis approach, wil describe the various contexts related to the formation social contruction of reality towards goverment financial statements as one of the public finance management artifacts inj indonesia . social reality is never as single one, what is understood about something that is socially contructed , may be (very) different from one to another. It relies on a series of processes known as externalitation, internalitation and objectivication. This series of processes will form the social contruction of a reality. In this contexts, a reality is not something given by nature, nor something scientifically estabilished, someone will contruct a social reality based on but not limited to his/her preference , knowledge or exprience As a socially constructed artifact, goverment financial statement also interpreted within its social context. This paper try to elaborates those interpretations. This study did not aim to estabilised as social conctruction of reality model, but rather to describe what social reality had been conctructed.